Major Royal Jelly Protein 2 (mrjp2) Gene in Apis cerana from Central Sulawesi, Indonesia - I Made Budiarsa; Manap Trianto; Akram Akram; Yulia Windarsih; Abdul Ashari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Indonesia is recognized as one of the world’s biodiversity hotspots, supporting a wide range of pollinating insects, including honey bee species of the genus Apis. Among these, Apis cerana is the most widely managed species and contributes significantly to national honey production, particularly in Sulawesi. However, the increasing economic value of honey has led to frequent cases of entomological origin fraud, in which honey is falsely labeled as being produced by a different bee species. This study aimed to determine the entomological origin of honey sold in Central Sulawesi using the Major Royal Jelly Protein 2 (mrjp2) gene as a molecular marker. Seven honey samples claimed as “forest honey” were analyzed through DNA extraction, PCR amplification using species-specific primers (CF-CR), and sequencing followed by BLAST-n analysis. All samples yielded high-quality DNA with purity ratios appropriate for PCR amplification. PCR successfully amplified the mrjp2 gene, producing fragments of approximately 201-208 bp, consistent with the expected size for A. cerana. Sequence analysis showed percent identity values ranging from 99.20% to 100% when compared with reference sequences of A. cerana. Based on molecular verification, three samples (H3, H5, and H7) did not match the seller’s claims and were confirmed to originate from A. cerana rather than A. dorsata binghami. These findings demonstrate that sequencing of the mrjp2 gene is an effective and reliable approach to authenticate the entomological origin of honey and to detect fraudulent labeling in commercial honey products.